Comparison of lower limb stiffness between male and female dancers and athletes during drop jump landings. (16th October 2018) - Ward, Rachel E.; Fong Yan, Alycia; Orishimo, Karl F.; Kremenic, Ian J.; Hagins, Marshall; Liederbach, Marijeanne; Hiller, Claire E.; Pappas, Evangelos
Abstract : Repetition of jumps in dance and sport training poses a potential injury risk; however, non‐contact landing injuries are more common in athletes than dancers. This study aimed to compare the lower limb stiffness characteristics of dancers and athletes during drop landings to investigate possible mechanisms of impact‐related injuries. Kinematics and kinetics were recorded as 39 elite modern and ballet dancers (19 men and 20 women) and 40 college‐level team sport athletes (20 men and 20 women) performed single‐legged drop landings from a 30‐cm platform. Vertical leg stiffness and joint stiffness of the hip, knee, and ankle were calculated using a spring‐mass model. Stiffness data, joint kinematics, and moments were compared with a group‐by‐sex 2‐way analysis of variance. Multiple linear regression was used to assess the relative contribution of hip and knee and ankle joint stiffness to variance in overall vertical leg stiffness for dancers and athletes. Dancers had lower leg ( P < 0.001), knee joint ( P = 0.034), and ankle joint stiffness ( P = 0.043) than athletes. This was facilitated by lower knee joint moments ( P = 0.012) and greater knee ( P = 0.029) and ankle joint ( P = 0.048) range of motion in dancers. Males had higher leg ( P < 0.001) and ankle joint stiffness ( P < 0.001) than females. This occurred through lower ankle range of motion ( P < 0.001) and greater ankle moment ( P = 0.022) compared to females. Male and female dancers demonstrated reduced lower limb stiffness compared to athletes, indicating a more pliable landing technique. Dance training techniques could potentially inform approaches to injury prevention in athletes.